Constructing Theme and Rheme Positions in Indonesian Humor: A Systemic Functional Linguistic Analysis - Yuwana, Rawuh Yuda; Betaubun, Martha (Journal of Language and Literature Studies, 2024)
Humor is one of the media that provides an interesting aspiration of people. It means comedians and audiences have to know how to imply and understand the real theme to get a good meaning. This study explores the construction of theme and rheme positions in Indonesian humor through the lens of Systemic Functional Linguistics (SFL). Utilizing the Theme-Rheme theory, the research analyzes various Indonesian clauses to understand how thematic structures contribute to comedic effects. The method involves a detailed breakdown of clauses into their thematic and rhematic components, followed by an examination of how marked and unmarked themes, as well as textual themes, create humor through incongruity and unexpected twists. Practically, the findings reveal that humor often applies from the contrast between serious advice and trivial or absurd explanations, demonstrating that thematic manipulation is crucial in generating comedic effects. This study highlights the effectiveness of the Theme-Rheme framework in analyzing humor and underscores the intricate relationship between language structure and humor.